Evaluating metastatic risk in breast cancer through CTCs and L1CAM expression - Liao, Ni; Guo, Qiong; Chen, Jingjing; Tan, Fulan; Huang, Yan; Yi, Jiansheng; Hu, Yi; Zeng, Chen; Ouyang, Qianhui; Chen, Zhouxi; Zhou, Wei (Frontiers in Oncology, 2025)
IntroductionCirculating tumor cells (CTCs) and L1 cell adhesion molecule (L1CAM) are associated with breast cancer (BC) metastasis. This study investigated their potential as predictive biomarkers for lymph node metastasis in early-stage invasive breast cancer (ESIBC).MethodsNinety-three ESIBC patients were enrolled. CTC phenotypes and L1CAM expression were detected in preoperative blood samples using the CanPatrol® CTC system and RNA-ISH. Associations with clinicopathological variables were analyzed.ResultsCTCs were detected in 79.6% of patients. Hybrid CTCs (H-CTCs) and L1CAM-positive CTCs were significantly correlated with lymph node metastasis and Ki-67 expression. A nomogram integrating H-CTCs, L1CAM, and Ki-67 predicted metastatic risk with excellent accuracy (AUC = 0.98).DiscussionH-CTCs and L1CAM-positive CTCs serve as potential blood-based biomarkers for evaluating metastatic risk in BC.ConclusionThe combined detection of H-CTCs and L1CAM enhances preoperative prediction of lymph node metastasis and provides new insights into BC metastasis mechanisms.